2019
DOI: 10.18488/journal.88.2019.51.17.28
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Unemployment in Nigeria: Effect of Real Exchange Rate and Inflation Interaction

Abstract: Article History KeywordsInflation Real exchange rate Unemployment Generalized moment method Marginal effect Interaction of real exchange rate and inflation.Contribution/Originality: This study contributes to the existing studies by distinguishing itself identifying the simultaneous impact of these two fluctuating variables (inflation rate and real exchange rate ) on unemployment, unlike existing literatures which addressed these impacts on unemployment separately and assessing how inflation influences the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…According to my knowledge, there was no one conducting the same interaction with my study. However, Olanrewaju (2019) conducted a similar interaction between inflation rate and exchange rate on the unemployment rate in Nigeria and found that the higher the inflation rate and real exchange rate depreciation, the unemployment increased.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to my knowledge, there was no one conducting the same interaction with my study. However, Olanrewaju (2019) conducted a similar interaction between inflation rate and exchange rate on the unemployment rate in Nigeria and found that the higher the inflation rate and real exchange rate depreciation, the unemployment increased.…”
Section: Discussionmentioning
confidence: 98%
“…For example, In Bangladesh, Chowdhury and Hossain (2014) utilized a simple single equation linear regression model (SELRM), In China, Chang (2005) applied the autoregressive distributed lag (ARDL) approach and In Bahrain, Alrayes and Abu Wadi (2018) used the ordinary least square (OLS) model. Furthermore, Olanrewaju (2019) examined the effect of real exchange rate and inflation interaction on unemployment in Nigeria by employing the generalized method of moments (GMM) technique in order to control the endogeneity of variables found that the higher the inflation rate and real exchange rate depreciation, the unemployment increased.…”
Section: Literature Reviewmentioning
confidence: 99%